The prevalence of postnatal depression and associated factors among clinic attendees in Maseru, Lesotho - Mokwena, Kebogile Elizabeth; Makhozonke, Ntombizotwa (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of the study was to screen for postnatal depression (PND) symptoms among women attending primary health care (PHC) facilities within Maseru City Council in Lesotho. The Edinburg Postnatal Depression Scale (EPNDS) was used to screen for PND symptoms in a sample of 393 postnatal mothers, and a quantitative questionnaire was used to collect socio-demographic data. The Pearson chi-test of association was used to explore associations between socio-demographic variables and EPND scores (p<0.05). The ages of the participants ranged from 17 to 40, with a mean of 27 years. Most were married (n = 310, 78.88%) and unemployed (n = 254, 64.63%), with high school as their highest level of education (n = 272, 69.21%). The majority (n = 312, 79.6%) had between 1 and 2 children. A third of the sample were HIV positive (n = 117, 29.77%). The prevalence of PND symptoms was 43%. Social support, financial support from the partner, relationships with the partner, knowledge of HIV status, and having experienced a severe financial crisis were significantly associated with PND symptoms. On multivariate logistic regression, only financial support from a partner and having experienced a severe financial crisis remained significantly associated with the development of PND (p = 0.05). Risk factors for PND are mostly socio-economic. The high prevalence of PND highlighted the need to integrate routine screening of mothers for PND, which will enable early diagnosis and treatment and thus contribute to the improvement of maternal and child well-being in the country.